Recent Publications (Quarterly Journal of Economics, 1947)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 61, Issue 4, August 1947, Pages 658–660, https://doi.org/10.1093/qje/61.4.658 Published: 01 August 1947